2022
DOI: 10.3390/jcm11030481
|View full text |Cite
|
Sign up to set email alerts
|

Anatabine, Nornicotine, and Anabasine Reduce Weight Gain and Body Fat through Decreases in Food Intake and Increases in Physical Activity

Abstract: Obesity is a leading cause of preventable death in the United States. Currently approved pharmacotherapies for the treatment of obesity are associated with rebound weight gain, negative side effects, and the potential for abuse. There is a need for new treatments with fewer side effects. Minor tobacco alkaloids (MTAs) are potential candidates for novel obesity pharmacotherapies. These alkaloids are structurally related to nicotine, which can help reduce body weight, but without the same addictive potential. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Other pyridine alkaloids produced by Nicotiana species, such as anatabine and anabasine, have recently been associated with beneficial medicinal properties for e.g. Alzheimer disease, chronic lymphocytic autoimmune (Hashimoto's) thyroiditis and obesity (Grebenstein et al., 2022; Schmeltz et al., 2014; Verma et al., 2015). The untargeted approach, used in the present study for volatile analysis, detected nicotine and four derived pyridine alkaloids: cotinine, nornicotine, myosmine and nicotyrine.…”
Section: Resultsmentioning
confidence: 99%
“…Other pyridine alkaloids produced by Nicotiana species, such as anatabine and anabasine, have recently been associated with beneficial medicinal properties for e.g. Alzheimer disease, chronic lymphocytic autoimmune (Hashimoto's) thyroiditis and obesity (Grebenstein et al., 2022; Schmeltz et al., 2014; Verma et al., 2015). The untargeted approach, used in the present study for volatile analysis, detected nicotine and four derived pyridine alkaloids: cotinine, nornicotine, myosmine and nicotyrine.…”
Section: Resultsmentioning
confidence: 99%
“…Dimethylethanolamine (N,N-dimethylethanolamine) is a colorless, volatile liquid with an unpleasant ammonia odor that may be associated with the heavy, earthy stench of wild duck eggs. Grebenstein et al (2022) showed that short-term daily administration of minor tobacco alkaloids (nornicotine, anatabine, and anabasine) produced a positive effect on weight loss by reducing body fat and food intake and increasing physical activity [ 58 ]. Linoleic acid is known to be an important fatty acid for both humans and animals.…”
Section: Discussionmentioning
confidence: 99%